Chambers McGraw-Hill first learners' dictionary - Brown, Amy L.; Downing, John.; Sceats, John. (London : McGraw-Hill, 1972)
This dictionary gives the meanings and sounds of about 5,000 simple English words. Where the dictionary gives two different pronunciations of a word, you will also find that it gives two meanings.
ne 27/08/2021
Ref.
Keywords: Learning